The Implementation of Qurban Worship in the Perspective of Sahih Hadith of Al-Bukhari: A Case Study of the Muslim Community in Tembung Village - Umar Akram; Muhammad Ali Azmi Nasution; Nurliana Damanik (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
This study aims to analyze the implementation of sacrificial worship in the perspective of authentic hadith of Al-Bukhari with a case study on the Muslim community in Tembung Village. The research method used is qualitative descriptive with a living hadith approach, which involves direct observation, interviews, and literature reviews of hadiths related to qurbani worship. The results of the study show that although the implementation of sacrificial worship in Tembung Village is generally in accordance with the guidance of Islamic law, there are several practices that are less than optimal in the application of the sunnah, such as the installment system in the purchase of sacrificial animals, sacrificing on behalf of the deceased, the mixing of sacrificial meat from various participants, to the provision of slaughterers' wages taken from the sacrificial animal parts. This study emphasizes the importance of a deep understanding of hadith as a source of Islamic law so that the practice of sacrificial worship can be carried out in accordance with the teachings of the Prophet Muhammad PBUH and have higher spiritual and social values